2019
DOI: 10.1016/j.molcel.2019.04.019
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiac Ryanodine Receptor Phosphorylation Hotspot Embraces PKA in a Phosphorylation-Dependent Manner

Abstract: Ryanodine receptors (RyRs) are intracellular Ca 2+ release channels controlling essential cellular functions. RyRs are targeted by cyclic AMP (cAMP)dependent protein kinase A (PKA), a controversial regulation implicated in disorders ranging from heart failure to Alzheimer's. Using crystal structures, we show that the phosphorylation hotspot domain of RyR2 embraces the PKA catalytic subunit, with an extensive interface not seen in PKA complexes with peptides. We trapped an intermediary open-form PKA bound to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 89 publications
(113 reference statements)
8
33
0
Order By: Relevance
“…The results further demonstrated that the addition of a phosphomimetic at the CaMKII site (S2814D), results in structural changes in the RyR2 phosphorylation domain that enhance the interaction with PKAc. These findings strongly suggest that phosphorylation of Ser 2814 site may affect the activity of PKA and impact on Ser 2808 , i.e., nearby phosphorylation sites might influence one each other (Haji-Ghassemi et al, 2019). This possible interaction among the different residues sharing the phosphorylation "hotspot" region of RyR2, might clarify previous controversial findings on the role of Ser 2808 site on different physiological and disease situations.…”
Section: Post-translational Modifications Of Ryr2mentioning
confidence: 51%
“…The results further demonstrated that the addition of a phosphomimetic at the CaMKII site (S2814D), results in structural changes in the RyR2 phosphorylation domain that enhance the interaction with PKAc. These findings strongly suggest that phosphorylation of Ser 2814 site may affect the activity of PKA and impact on Ser 2808 , i.e., nearby phosphorylation sites might influence one each other (Haji-Ghassemi et al, 2019). This possible interaction among the different residues sharing the phosphorylation "hotspot" region of RyR2, might clarify previous controversial findings on the role of Ser 2808 site on different physiological and disease situations.…”
Section: Post-translational Modifications Of Ryr2mentioning
confidence: 51%
“…Therefore, there could be mutual allosteric interactions between various RyR2 phosphorylation sites, where phosphorylation of one site may change the protein kinase and/or phosphatase affinity of another site in the same RyR2 macromolecular complex (Haji‐Ghassemi et al . ). In this view, the chronic removal of one site may potentially lead to similar adaptive changes, making it even more challenging to determine the co‐operation among the various phosphorylation sites.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, a crystal structure of the mouse RyR2 Repeat3–4 domain bound to the catalytic domain of PKA (PKAc) in complex with the non-hydrolyzable ATP analog adenylyl-imidodiphosphate (AMP-PNP) was determined [ 168 ]. In this structure, PKAc was in a non-catalytic open conformation and the phosphorylation loop of Repeat3–4 was found to encircle the large lobe of PKAc.…”
Section: Structural Studies Of the Ryr1 And Ryr2 Isoformsmentioning
confidence: 99%